The Importance of Cl− Exclusion and Vacuolar Cl− Sequestration: Revisiting the Role of Cl− Transport in Plant Salt Tolerance - Wu, Honghong; Li, Zhaohu (Frontiers in plant science, 2019)
Salinity threatens agricultural production systems across the globe. While the major focus of plant researchers working in the field of salinity stress tolerance has always been on sodium and potassium, the transport patterns and physiological roles of Cl- in plant salt stress responses are studied much less. In recent years, the role of Cl- in plant salinity stress tolerance has been revisited and has received more attention. This review attempts to address the gap in knowledge of the role of Cl- transport in plant salinity stress tolerance. Cl- transport, Cl- exclusion, vacuolar Cl- sequestration, the specificity of mechanisms employed in different plant species to control shoot Cl- accumulation, and the identity of channels and transporters involved in Cl- transport in salt stressed plants are discussed. The importance of the electrochemical gradient across the tonoplast, for vacuolar Cl- sequestration, is highlighted. The toxicity of Cl- from CaCl2 is briefly reviewed separately to that of Cl- from NaCl.Salinity threatens agricultural production systems across the globe. While the major focus of plant researchers working in the field of salinity stress tolerance has always been on sodium and potassium, the transport patterns and physiological roles of Cl- in plant salt stress responses are studied much less. In recent years, the role of Cl- in plant salinity stress tolerance has been revisited and has received more attention. This review attempts to address the gap in knowledge of the role of Cl- transport in plant salinity stress tolerance. Cl- transport, Cl- exclusion, vacuolar Cl- sequestration, the specificity of mechanisms employed in different plant species to control shoot Cl- accumulation, and the identity of channels and transporters involved in Cl- transport in salt stressed plants are discussed. The importance of the electrochemical gradient across the tonoplast, for vacuolar Cl- sequestration, is highlighted. The toxicity of Cl- from CaCl2 is briefly reviewed separately to that of Cl- from NaCl.